2020
DOI: 10.1007/s00134-020-06031-4
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and extra-corporeal membrane oxygenation in adult patients: a systematic review and meta-analysis

Abstract: Despite increasing improvement in extracorporeal membrane oxygenation (ECMO) technology and knowledge, thrombocytopenia and impaired platelet function are usual findings in ECMO patients and the underlying mechanisms are only partially elucidated. The purpose of this meta-analysis and systematic review was to thoroughly summarize and discuss the existing knowledge of platelet profile in adult ECMO population. All studies meeting the inclusion criteria (detailed data about platelet count and function) were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 55 publications
(141 reference statements)
10
80
0
Order By: Relevance
“…Abrams first stated that platelet count reduction was mostly due to the severity of the disease of patients rather than related to the duration of ECMO support [57]. In a recent meta-regression, we confirmed that a worsening in thrombocytopenia was independent of the number of days on ECMO [56]. However, we speculated that after few days the inflammatory response induced by ECMO might not affect the freshly generated platelets due to the beginning of an endothelization mechanism of the circuit [56,61,62].…”
Section: Platelets and Extracorporeal Membrane Oxygenationsupporting
confidence: 56%
See 3 more Smart Citations
“…Abrams first stated that platelet count reduction was mostly due to the severity of the disease of patients rather than related to the duration of ECMO support [57]. In a recent meta-regression, we confirmed that a worsening in thrombocytopenia was independent of the number of days on ECMO [56]. However, we speculated that after few days the inflammatory response induced by ECMO might not affect the freshly generated platelets due to the beginning of an endothelization mechanism of the circuit [56,61,62].…”
Section: Platelets and Extracorporeal Membrane Oxygenationsupporting
confidence: 56%
“…The ECMO mode also does not seem to influence the degree of thrombocytopenia [56]. After analyzing the available evidence in the literature, we estimated a comparable platelet count decrease in almost 25% and 23% of adult V-A and V-V ECMO subjects, respectively [56].…”
Section: Platelets and Extracorporeal Membrane Oxygenationmentioning
confidence: 80%
See 2 more Smart Citations
“…Although thrombocytopenia is frequent in critically ill patients, the incidence of HIT is relatively rare (<1% 3 ; up to 3.7% in patients supported by extracorporeal membrane oxygenation). 4 In a previously published cohort of 105 patients supported by venovenous extracorporeal membrane oxygenation, we reported an incidence of HIT of 2% 5 compared with 3 among 14 patients (21%) during the COVID-19 pandemic. We compared this cohort with a control cohort of patients in the intensive care units of our centers during a 6-month period from January 1 to June 1, 2019: 447 patients were admitted to our centers, with 58.8% of patients requiring mechanical ventilation and 13 patients (5%) supported by extracorporeal membrane oxygenation.…”
mentioning
confidence: 86%